Combination of lipopolysaccharide and hypoxia-ischemia attenuates cholinergic anti-inflammatory effect in newborn rat brains - S. Furukawa; L. Yang; H. Sameshima (IMR Press, 2020)
Aim: Pharmacologic parasympathetic nerve stimulation markedly reduces brain damage in a newborn rat model of hypoxia-ischemia (HI). Our aim is to determine whether a brain-protective effect can be achieved by parasympathetic nerve stimulation even with the synergy effect of lipopolysaccharide (LPS) and HI. Study design: 7-day-old Wistar rats were used. Rats received intraperitoneal administration of LPS which was followed by left carotid artery ligation. After a two-hour recovery period rats were placed in a hypoxic environment (8% oxygen) for 1 hour. Carbachol, used as an acetylcholine receptor agonist, or saline was injected subcutaneously immediately prior to one-hour hypoxia to determine its neuroprotective effect. Seven days later, the degree of brain damage in the ligated side of the hemisphere was compared to that in the contralateral hemisphere, which acts as reference. The relative difference in hemisphere area ((ligated side/non-ligated side) × 100%) was employed as an indicator of brain damage. Microglial aggregation (cells/mm 2) on the cortex and cytokine production in the ligated side of the hemisphere were also evaluated. Results: Three pups died in the carbachol group. There was no significant difference in brain damage between the saline (n = 34) and carbachol (n = 30) groups (86.0 ± 12.1% vs. 90.8 ± 13.6%, respectively). There was no significant difference in microglial aggregation between the saline and carbachol groups (155.7 ± 201.1 cells/mm2 vs. 89.8 ± 149.1 cells/mm2, respectively). IL-1β production in the saline and carbachol groups was 1.8 ± 1.2 pg/dL and 1.8 ± 1.1 pg/dL, respectively, with no significant difference between the groups. Conclusion: Combination of LPS and HI attenuates cholinergic anti-inflammatory effect in newborn rat brains.